Dual form of training as a problem of pedagogical research - Svetlana O. Fominykh (Russian Journal of Education and Psychology)
Background. This article is devoted to the study of the pedagogical aspects of the problem of the dual form of education. In the modern world of intensive introduction of high technologies into all spheres of human life, the need for the formation of a system of training highly qualified specialists who meet the increased requirements of employers is sharply increasing. As a solution to this problem, the dual form of education is implemented in the system of vocational education. This form provides an opportunity for enterprises and organizations to actively participate in the process of training personnel "for themselves" and gives a unique opportunity for students to integrate studies with real work experience. This not only allows you to acquire theoretical knowledge, but also to develop direct skills necessary for a successful career in a dynamically developing world.